Gene material delivering into plant cells using carbon nanotubes - Burlaka, O. M.; Pirko, Ya. V.; Yemets, A. I.; Blume, Ya. B. (Reports of the National Academy of Sciences of Ukraine, 2015)
Genetic transformation of Nicotiana tabacum L. protoplasts, callus and leaf explants with plasmid DNA pGreen0029, using carbon nanotubes (CNTs) non-covalently functionalized with biological molecules as nanocarriers, is conducted. Transient expression of the reporter yellow fluorescent protein YFP gene in protoplasts is shown. Stable transformation of callus and leaf discs with nptII gene resulted in the regeneration of transformed N. tabacum plants on a selective culture medium containing 50 mg/l kanamycin. Single-walled CNTs-based nanocarriers demonstrated their applicability to the transformation of protoplasts, as well as walled plant cells. Whereas, the developed multiwalled CNTs-based nanocarriers were less efficient for the targeted gene transfer, especially into cells of callus and leaf explants, primarily due to the restrictive role of cellulose walls for their penetration into cells and because of their larger diameter, resulting in a damage to the recipient cells.